Effect of stocking density on growth performance of African catfish Clarias gariepinus and water spinach Ipomoea aquatica in aquaponics systems with the addition of AB mix nutrient - Wiyoto Wiyoto; Ridwan Siskandar; Ratih Kemala Dewi; Wida Lesmanawati; Muhammad Arif Mulya; Julie Ekasari (Jurnal Akuakultur Indonesia)
Aquaponics is the cultivation of fish and plants in a series of systems, either in one container or in separate containers, by paying attention to the balance between fish, plants, and aquatic microorganisms. One of the obstacles in aquaponic activities is that vegetable growth is not optimal due to a lack of dissolved nutrients, so further research is needed to make better plant growth. This study aimed to evaluate catfish and water spinach growth performance in an aquaponic system by adding AB mix nutrients at different fish stocking densities. This study used a completely randomized design with three differences in stocking densities of catfish (150 fish/m3, 200 fish/m3, and 250 fish/m3) as test animals with four replications where AB mix was added to each treatment. The growth performance of catfish is better in control with a stocking density of 250 fish/m3 and without adding nutrients. The growth performance of catfish decreased with the addition of AB mix nutrients, while the growth of water spinach was better. The growth rate of catfish without adding AB mix nutrients was higher than in other treatments. In contrast, all treatments with the addition of AB mix increased the growth performance of water spinach, with the stocking density of catfish not affecting the growth of water spinach plants.